Main Metabolic Pathways of TAK-802, a Novel Drug Candidate for Voiding Dysfunction, in Humans: The Involvement of Carbonyl Reduction by 11β-hydroxysteroid Dehydrogenase 1 - Nishihara, M.; Takahashi, J.; Kondo, T.; Mouri, K.; Asahi, S. (Drug Research, 2014)
To investigate species differences in the metabolism of TAK-802, in vitro and in vivo metabolic profiles were compared between humans and animals. TAK-802 was mainly metabolized to M-I, M-II, M-III and M-IV in human and animal liver microsomes. Especially the M-IV formation in humans was greater than that in animals. Likewise, M-IV was detected to a lower extent in the plasma and excreta of animals administered with TAK-802, whereas the AUC0–48 h of M-IV was approximately five-fold higher than that of TAK-802 in human plasma. These results indicate that the in vitro metabolic profile reflects the in vivo condition. Thus, to identify the metabolic pathway of TAK-802 in humans, the responsible enzyme to form M-IV was elucidated in vitro. Since M-IV is a reductive metabolite formed in microsomes, the possibility of involvement of 11β-hydroxysteroid dehydrogenase (11β-HSD), a carbonyl reductase located in microsomes, was first investigated. Consequently, M-IV formation was confirmed by incubation with human 11β-HSD1-expressing microsomes and was concentration-dependently inhibited by glycyrrhetinic acid, an inhibitor for 11β-HSD enzymes, indicating the involvement of 11β-HSD1 in the M-IV formation. In contrast, little M-IV formation was observed using rat 11β-HSD1, suggesting species differences between humans and rats. In addition, M-II was formed via M-IV, not via M-I and the CYP identification studies revealed that both M-I formation from TAK-802 and M-II formation from M-IV were mainly catalyzed by CYP3A4. In conclusion, 11β-HSD1 and CYP3A4 are principally responsible for the metabolism of TAK-802 in humans and 11β-HSD1 may be responsible for the observed species difference.
Keywords: TAK-802; 11β-hydroxysteroid dehydrogenase (11β-HSD); CYP; metabolism; species difference